Study the dose profile of low energy electron accelerator. Issue 1 (March 2021) - Wah, Leo Kwee; Azhar, M.; Chulan, R. M.; Hashim, S. A.; Mokhtar, M.; Khaidawaton,; Baijan, H.; Sabri, R. M.
Abstract: This paper describes dose mapping method for Low Energy Electron Accelerator (LEEA). This locally designed LEEA with the former energy of 140 keV will be upgraded to 300 keV. In the setup, the electron beam is energized by the electric field with high voltage power supply, scanning and passing through the titanium foil, to irradiate the sample. The dose profile by the energetic beam mapping results have been obtained by using Cellulose Triacetate (CTA) dosimeter.